Yagyu Ninja Scrolls 6 - Segawa, Masaki (Kodansha, 2021)
VENGEANCE! The Hori women have defeated three of the Aizu Seven Spears-so now Lord Akinari, their ultimate target, is on the defense. He's beaten a hasty retreat to his home, and the women have split into two groups in order to hunt him down. Will they finally take their revenge against the wicked Akinari?